Impact of nitrogen fertilization on growth, yield and glycoside content of stevia (Stevia rebaudiana Bertoni) - Abd Ghani, Rosnani (2014)
Stevia, a well-known crop with sweet taste and zero calorie is an ideal substitute for cane sugar. There is currently an increasing demand for non-sugar sweeteners such as stevia due to the heightened health consciousness among consumers to reduce sugar intake to combat diabetes. Nitrogen is an important nutrient in stevia cultivation as it promotes leaf growth which is the economic component of stevia. Two glasshouse experiments were carried out in this study. The first experiment was conducted to determine optimum rate of nitrogen (N) and to compare two frequencies of N application for stevia. Urea was used as a source of N fertilizer in this study. The plant was planted as a ratoon crop and a total of four harvests were taken. Factorial combinations of seven N rates (0, 50, 100, 150, 200, 250 and 300 kg ha-1 ) and two application frequencies (every 30 days and every 60 days) were evaluated for their effects on stevia yield and sweetness quality. Results showed that N rates and fertilizer application frequencies had significant influence on biomass yield, glycosides content, glycosides yield and sweetness quality of stevia. Based on biomass yield the best N rate for stevia was 260 kg ha-1 and the application interval of 30 days was better than 60 days. The total fresh yield and dry yield from four harvests were 37 t ha-1 and 6.2 t ha-1, respectively. On the other hand, the glycoside content was superior at low N rates. The highest stevioside (ST) and rebaudioside-A (Reb-A) concentration was obtained at 0 N (control) (85 mg g-1 for ST, 21 mg g-1 for Reb-A). When biomass yield was multiplied with glycoside content to give glycoside yield, the best N rate was 160 – 210 kg N ha-1 with 60 days interval of application that gave ST yield of 410 kg ha-1 and Reb-A yield of 85 kg ha-1. Nevertheless, the most important factor in stevia production is their sweetness quality. With higher concentration of Reb-A, the sweetness and quality of stevia is much greater. Based on the sweetness quality, 50 kg N ha -1 was the best rate for stevia with fertilizer applied at 30 days interval. At this rate and frequency, the ratio Reb-A to the ST was 0.4. The second experiment was carried out to evaluate response of stevia to the different sources of nitrogen fertilizer. The treatments comprised of a control (0 N), one inorganic source (urea) and three organic sources of N which were chicken dung, goat dung and worm casting. Biomass yield was higher in plants treated with urea compared to those treated with organic fertilizers. The glycoside content ST was significantly higher at 0 N (113.60 mg g-1) followed by chicken dung (110.76 mg g-1). However, the highest Reb-A content was in plants treated with chicken dung (10.41 mg g-1) followed by 0 N treatment. The application of chicken dung also produced significantly higher amount of ST yield (333.23 kg ha-1) and Reb-A yield (31.30 kg ha-1 ). The sweetness quality was better when chicken dung and goat dung were used with ratio of Reb-A to the ST respectively at 0.094 and 0.091. In conclusion, optimum N rate in stevia production was 260 kg ha-1 based on biomass yield and 50 kg ha-1 based on sweetness quality. The fertilizer application interval of 30 days was more suitable for stevia compared to application of every 60 days. The use of chicken dung or goat dung gave high sweetness quality of stevia and it was recommended as a better nitrogen fertilizer source compared to the inorganic source, urea.